2017
DOI: 10.1002/cne.24270
|View full text |Cite
|
Sign up to set email alerts
|

Inferior olivary projection to the zebrin II stripes in lobule IXcd of the pigeon flocculus: A retrograde tracing study

Abstract: Zebrin II (ZII; a.k.a. aldolase C) is expressed heterogeneously in Purkinje cells (PCs) such that there are sagittal stripes of high expression (ZII+) interdigitated with stripes of little or no expression (ZII-). The pigeon flocculus receives visual-optokinetic information and is important for generating compensatory eye movements. It consists of 4 sagittal zones based on PC complex spike activity (CSA) in response to rotational optokinetic stimuli. There are two zones where CSA responds best to rotation abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 125 publications
(181 reference statements)
1
15
0
Order By: Relevance
“…We have shown that they receive CF input from separate, but adjacent areas of the mcIO (Fig. 4 c) [ 81 , 82 ], and there is some suggestion that the ZII+ and ZII− PCs have differential projections [ 76 ]. We have some evidence that the CSA of ZII+ PCs shows a greater depth of modulation to optic flow stimuli, compared to the ZII− PCs within the same functional unit [ 83 ].…”
Section: Optic Flow Modules In the Vestibulocerebellum Of Pigeons (Dmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that they receive CF input from separate, but adjacent areas of the mcIO (Fig. 4 c) [ 81 , 82 ], and there is some suggestion that the ZII+ and ZII− PCs have differential projections [ 76 ]. We have some evidence that the CSA of ZII+ PCs shows a greater depth of modulation to optic flow stimuli, compared to the ZII− PCs within the same functional unit [ 83 ].…”
Section: Optic Flow Modules In the Vestibulocerebellum Of Pigeons (Dmentioning
confidence: 99%
“…Best-known examples of the functional properties of cerebellar modules are illustrated by the ample bulk of research studying the adaptive control of reflexive eye and head movements. Here, individual floccular modules control movements around a particular visual axis [ 82 , 236 , 237 ]. However, it should be noted that also in the vestibulocerebellum, several non-adjacent zones seem to be present with basically the same function [ 71 ].…”
Section: Toward a Description Of The Functional Modular Organization mentioning
confidence: 99%
“…Finally, lateral to this and spanning the lateral half of P2+ (P2+lat) and the P2− stripe, is a zone containing neurons responsive to optic flow resulting from “descent”. Previously we have shown that the inputs to the ZII+ and ZII− stipes in the flocculus (i.e., stripes P4+/− to P6+/−) receive CF input from separate, but adjacent areas of the inferior olive (IO; Wylie et al, 2017 ). The ZII+ stipes within the VA zones (P4+ and P6+) receive input from the caudal-most portion of the mcIO while the ZII− stripes of the VA zones (P4− and P6−) are innervated by a slightly more rostral region of the mcIO.…”
Section: Introductionmentioning
confidence: 98%
“…In the pigeon vestibulocerebellum (VbC), we have shown that the ZII stripes coincide with functional properties of PCs and afferent inputs (Pakan and Wylie, 2008 ; Pakan et al, 2010 , 2011 , 2014 ; Graham and Wylie, 2012 ; Wylie et al, 2013 , 2017 ). The avian VbC, which consists of folia IXcd and X, contains PCs whose complex spike activity (CSA) are responsive to optic flow patterns resulting from self-motion (Wylie and Frost, 1991 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation